Prevalence and electrophysiological phenotype of rare SCN5A genetic variants identified in unexplained sudden cardiac arrest survivors. Issue 4 (24th February 2020) - Giudicessi, John R; Ye, Dan; Stutzman, Marissa J; Zhou, Wei; Tester, David J; Ackerman, Michael J
Abstract: Aims: To determine the prevalence and in vitro electrophysiological (EP) phenotype of ultra-rare SCN5A variants of uncertain significance (VUS) identified in unexplained sudden cardiac arrest (SCA) survivors. Methods and results: Retrospective review of 73 unexplained SCA survivors was used to identify all patients that underwent a form of genetic testing that included comprehensive SCN5A analysis. Ultra-rare SCN5A variants (minor allele frequency < 0.005) were adjudicated according to the 2015 American College of Medical Genetics and Genomics (ACMG) guidelines. Variants designated as VUS were expressed heterologously and characterized using the whole-cell patch clamp technique. Overall, 60/73 (82%; the average age at SCA 28 ± 12 years) unexplained SCA survivors had received SCN5A genetic testing. Of these, 5/60 (8.3%) had an ultra-rare SCN5A variant. All SCN5A variants were classified as VUS. Whereas the single SCN5A VUS (p.Asp872Asn-SCN5A) identified in an unexplained SCA survivor with PR interval prolongation and inferior early repolarization conferred a loss-of-function phenotype (46.2% reduction in peak current density; 16 ms slower recovery from inactivation), the four other SCN5A VUS (p.Glu30Gly-SCN5A, p.Gln245Lys-SCN5A, p.Pro648Leu-SCN5A, and p.Glu1240Gln-SCN5A) identified in unexplained SCA survivors without early repolarization/conduction delay were indistinguishable from wild-type Nav 1.5 channels. Conclusion: In the absence of a phenotype(s) potentially attributable to sodium channel dysfunction, all SCN5A VUS identified in unexplained SCA survivors conferred a wild-type EP phenotype in vitro . As the background rate of SCN5A genetic variation is not trivial, great care must be taken to avoid prioritizing genotype over phenotype when attempting to ascertain the root cause of an individual's SCA.